Гещалт психология и уеб дизайн – принципи, закони, практики [Gestalt psychology and web design – principles, laws, practices] - Valkanova, Vesselina (Годишник на Софийския университет „Св. Климент Охридски”, Факултет по журналистика и масова комуникация [Annual of Sofia University „St. Kliment Ohridski”, Faculty of Journalism and Mass Communication], 2017)
The article analyzes the basic principles and lows of the gestalt psychology, explaining the rules according to which certain elements, as mutually pertinent parts of the whole, are likely to be perceived: emergence, transportability, the tendency towards the simplest gestalt, the tendency towards isolation, the hierarchical structure of the gestalt, the laws of proximity, similarity, closure, symmetry etc. The main principles of web design and the use of gestalt psychological laws on design are discussed. During the perception of web design in the human brain take place active processes of judgment, interpretation, categorization and hierarchy of the elements, sifting important from unimportant, connecting similar components and creating structures that support perception.
https://katalog.adlr.link/Record/ai-53-585219